Technology Entrepreneurship Project (ENT 600) : Trina Solar / Raja Nur Farhana Raja Noor Kamal - Raja Noor Kamal, Raja Nur Farhana (2021)
Trina Solar is one of the world largest company that produce solar panels. As a vertically integrated company, Trina Solar controls, minimize risk and enhance return on investment (ROI) for their PV systems throughout the entire supply chain. In this company analysis, Trina Solar which is in the category of solar product supplier, the company will be the main focus. The analysis includes the identification of strength, product problems and the solutions for the problems. Some difficulties with the solar panels production can be identified throughout the analysis. Firstly, the solar inefficiency caused by insulation resistance, environmental conditions and solar panel types. Although the installed solar panels are thought to be in good condition, they can sometimes be overlooked and damage can happen. Isolation resistance occurs when the leak occurs on the edges of solar panels. If damage occurred to solar panels, a higher voltages system will be bothered. The other problem is that the solar panel can produce toxic waste. Solar panels often contain leads, cadmium and other toxic chemicals which needed to be removed by breaking the entire solar panel apart. However, there are solutions that can be implemented in order to resolves all those problems. In order to increase the efficiency of the solar panel, high concentrated photovoltaic (CPV) can be used in the manufacturing of the solar panels. The efficiency of this CPV panels can reach up to 46% efficiency compared to the traditional solar panel with only 22% efficiency. The next problem can be resolved by properly manage the waste through recycled process. Recycled solar panels are surely reusable. Through the year of research into waste recycling of solar panels, many technologies are developed to aid the recycling process and increased the efficiency of waste handling by approximately 96%.